Photodynamic therapy in patients with skin metastases of disseminated melanoma - D. A. Tzerkovsky; N. A. Petrovskaya; A. N. Mazurenko (Biomedical Photonics, 2019)
The aim of the study was to evaluate the immediate results of photodynamic therapy (PDT) in patients with intradermal metastases of skin melanoma. The study included 50 patients who received treatment at the department of hyperthermia and photodynamic therapy. The study included 23 (46%) men and 27 (54%) women with an average age of 60.7±10.4 years. PDT of tumors was carried out 3–4 hours after intravenous administration of a chlorine-based photosensitizer (Photolon) in doses of 1.5–3 mg/kg using a semiconductor laser «UPL-PDT» (Lemt, Belarus, λ=660±5 nm). The exposure doses varied from 100 to 400 J/cm2; power density – from 0.2 to 0.9 W/cm2; power – from 0.25 to 1 W and time of PDT of one focus was dependent on the size and location of the tumor and was 5 to 20 minutes. Evaluation of antitumor efficacy of PDT was carried out according to WHO criteria. The terms of follow-up of patients were between 3 and 23 months. At follow-up observation, 1–3 months after the treatment, complete regression of intradermal metastases of skin melanoma was achieved in 9 (18%) patients, partial – in 28 (56%), process stabilization in 8 (16%) and progression in 5 (10%)) patients. The objective effect was achieved in 74% of patients, the therapeutic – in 90%. PDT can be used in the treatment of intradermal metastases of disseminated skin melanoma with palliative purposes and allows reducing the tumor volume, which significantly improves the quality of life of patients.